2016
DOI: 10.1089/neu.2014.3812
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Experimental Strategies Aimed at Improving Motor Function after Acute and Chronic Spinal Cord Injury

Abstract: While various approaches have been proposed in clinical trials aimed at improving motor function after spinal cord injury in humans, there is still limited information regarding the scope, methodological quality, and evidence associated with single-intervention and multi-intervention approaches. A systematic review performed using the PubMed search engine and the key words ''spinal cord injury motor recovery'' identified 1973 records, of which 39 were selected (18 from the search records and 21 from reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 55 publications
0
50
0
1
Order By: Relevance
“…In the United States alone, ∼30 individuals sustain a spinal cord injury every day (Gomes-Osman et al, 2016), typically caused by motor vehicle accidents (38%), falls (>22%), violence (13.5%), and sports and recreational accidents (9%). Diseases can also cause or increase the risk of spinal cord injury (National Spinal Cord Injury Statistical Center, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States alone, ∼30 individuals sustain a spinal cord injury every day (Gomes-Osman et al, 2016), typically caused by motor vehicle accidents (38%), falls (>22%), violence (13.5%), and sports and recreational accidents (9%). Diseases can also cause or increase the risk of spinal cord injury (National Spinal Cord Injury Statistical Center, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The most common causes of SCI are motor vehicle accidents (38%), falls (22%), violence (13.5%), and sport/recreational accidents (9%). 1 In SCI, structural and functional damage of the spinal cord occurs by primary and secondary injury. This results in loss of movement and sensation and sphincter and autonomic nerve dysfunction below the damaged plane.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for an overview of the available published locomotor training studies in persons with SCI, the reader is referred to a systematic review on this topic. 8 While there is great interest in the potential of pharmacological, biological, and genetic interventions to improve walking function in persons with SCI, 9 at this time the efficacy of these approaches in humans has not been established. A recent systematic review of the experimental strategies aimed at improving motor function in persons with SCI concluded that multi-intervention approaches that contain a rehabilitation component currently have the best evidence to support their value.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of the experimental strategies aimed at improving motor function in persons with SCI concluded that multi-intervention approaches that contain a rehabilitation component currently have the best evidence to support their value. 9 While early training approaches to improve locomotor function in persons with SCI focused on activating spinal central pattern generator (CPG) circuits associated with locomotor behavior, 10,11 there has been growing recognition of the role of spared supraspinal pathways in locomotor function. For this reason, recent studies have begun to target supraspinal control mechanisms in both animal models 12,13 and humans.…”
Section: Introductionmentioning
confidence: 99%